Neurological Uniqueness: A Case Study of Hepatitis A-Induced Acute Inflammatory Demyelinating Polyneuropathy - Abubakar, Azzaki; Murdia, Murdia; Diana, Diana (Indonesian Journal of Case Reports, 2023)
Acute inflammatory Demyelinating Polyneuropathy (AIDP) with hepatitis A (HA) is more likely to affect men, develop at a younger age, and have a better prognosis overall. The progression of the Hepatitis A Virus (HAV)-caused liver inflammation and the neurological difficulties could lead to AIDP in the early stages of the hepatitis signs and symptoms. The World Health Organization (WHO) estimates 1.5 million clinical HAV cases annually. Extrahepatic complications of this disease are rare. The etiology of HA associated AIDP remains unclear, with cross-reactive HA epitopes between the peripheral nervous system and other authors have hypothesized that the presence of CSF antibodies reflects direct entry into the central nervous system. Our patient presentations favored AIDP most commonly in HA. A 22-year-old man, with no prior significant medical history, presented to neurology emergency with a 3-day history of acute onset, had been complaining of nausea, general weakness, yellowing of the sclera and history of fever for 5 days. Further investigation revealed marked elevation of liver enzymes in a pattern suggestive of hepatocellular processes. Serum titres of hepatitis B, C, and E were negative, but IgM anti-HAV was positive (enzyme immunoassay). Elevation of Cerebrospinal fluid (CSF) protein and myelitis transversa shown by magnetic resonance imaging were established. The diagnosis as AIDP was taken and treated by symptomatic and neurology treatment. However, the patient regained strength and underwent physiotherapy during two weeks. Approximately 3 months after discharged, the patient's gait had nearly returned to baseline at follow-up and the symptoms slowly improved.